Longitudinal Associations Between Depression, Anxiety, Pain, and Pain-Related Disability in Chronic Pain Patients. Issue 3 (April 2015) - Lerman, Sheera F.; Rudich, Zvia; Brill, Silviu; Shalev, Hadar; Shahar, Golan
ABSTRACT Objective The current study sets out to examine the longitudinal relationship between pain, pain-related disability, and symptoms of depression and anxiety. The latter symptoms are highly prevalent in chronic pain and seriously impede functioning and quality of life. Nevertheless, the direction of the relationship involving these variables among individuals with chronic pain is still unclear. Methods Four-hundred twenty-eight individuals with chronic pain (238 women, mean age 54.84 years, mean pain duration 85.21 months) treated at two pain clinics completed questionnaires regarding their pain (Short-Form McGill Pain Questionnaire), depression (Center for Epidemiological Studies–Depression Scale), state anxiety (State-Trait Anxiety Inventory), and pain-related disability (Pain Disability Index) at four time points, with an average of 5 months between measurements. Cross-lagged, structural equation modeling analyses were performed, enabling the examination of longitudinal associations between the variables. Results Significant symptoms of both depression and anxiety were reported by more than half of the sample on all waves. A latent depression/anxiety variable longitudinally predicted pain (β = .27, p < .001) and pain-related disability (β = .38, p < .001). However, neither pain (β = .10, p = .126) nor pain-related disability (β = −.01, p = .790) predicted depression/anxiety. Conclusions Among adult patients with chronic pain treated at specialty pain clinics, high levels of depression and anxiety may worsen pain and pain-related disability.